Incidence of severe maternal outcomes following armed conflict in East Gojjam zone, Amhara region, Ethiopia: using the sub-Saharan Africa maternal near-miss criteria - Kebede, Tirusew Nigussie; Abebe, Kidist Ayalew; Malede, Ambachew Getahun; Sisay, Abinet; Yirdie, Ayenew; Taye, Worku; Moltot Kitaw, Tebabere; Fente, Bezawit Melak; Tadese, Mesfin; Demisse, Tesfanesh Lemma; Silesh, Mulualem; Beshah, Solomon Hailemeskel; et al. (Frontiers in Public Health, 2025)
BackgroundSevere maternal outcome (SMO) encompasses women who survive life-threatening conditions either by chance or due to treatment quality, or who die. This concept assumes that severe maternal morbidity predicts mortality risk, enabling the analysis of risk factors for life-threatening outcomes and improving our understanding on the causes of maternal death. This study aims to determine the incidence of SMO and its leading causes in East Gojjam during a period of regional conflict.MethodsA prospective follow-up study was conducted at Debre Markos Comprehensive Specialized Hospital in East Gojjam from July 1, 2023, to February 30, 2024. The study included 367 women admitted with potentially life-threatening conditions, including 8 maternal deaths, using sub-Saharan Africa (SSA) and WHO Maternal Near-Miss (MNM) criteria. Data were entered into Epi Data v.4.6 and analyzed using SPSS v.27. The WHO MNM approach assessed SMO indicators and maternal health care quality were utilized.ResultsDuring the eight-month period, there were 3,167 live births, 359 potentially life-threatening conditions (PLTC), and 188 SMO cases (180 MNM and 8 maternal deaths). The SMO ratio was 59.4 per 1,000 live births (95% CI: 51, 68 per 1,000 live births). The MNM to mortality ratio, mortality index, and maternal mortality ratio were 22.5:1, 4.2%, and 252.6 per 100,000 live births, respectively. Over 80% of women with SMO showed evidence of organ dysfunction upon arrival or within 12 h of hospitalization. The leading causes of SMO were hypertensive disorders of pregnancy (HDP) and obstetric hemorrhage, including uterine rupture, with uterine rupture contributing to half of the maternal deaths.ConclusionThis study found that the incidence of SMO was comparable to that reported in most other studies. HDP was the primary cause of SMO, followed by obstetrical hemorrhage, consistent with other studies in Ethiopia. Uterine rupture was identified as the leading cause of maternal death. As this study was conducted in a single institution and in the period of severe armed conflict, it may not fully capture the range of maternal health issues across populations with varying healthcare access and socio-economic backgrounds. Caution should be exercised when generalizing these findings to the wider population.